Habilidades pre-lectoras en estudiantes de primer grado de primaria en instituciones educativas de Ventanilla - Saurino Santillán, Urcina (2012)
This descriptive simple research aimed to determine the level of development achieved by the first grade primary students regarding pre-reading skills. The sample were 100 children from 3 public schools in Ventanilla, aged 6 – 7 years. The Predicting Reading Test (P.P.L.) of Bravo (1995) and adapted by Melendez and Morocho (2007) was applied to measure the phonological, semantic, and syntactic aspects of oral language. The results showed that only 13% of the students reached a high and superior level in pre-reading skills, while 53% reached a low and inferior level in the same skills. We concluded that the largest percentage of these students lack of there pre-requisites/ pre-requirements.